Representasi Kelas dan Kritik Sosial Terhadap Konformitas dalam Konten Youtube Tretan Universe Bersama Mutant - Moh. Alex Arifin; Ummi Maulidatus Syahro; Nurhasani Nurhasani; Ahmad Ilzamul Hikam (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study analyzes Tretan Muslim's Mutant series as a digital cultural text containing social criticism through the approach of Karl Marx's literary sociology. Amidst the limited academic studies on digital humor as a medium of social representation, this study investigates how class relations, social conformity, and symbolic domination are represented through the humorous interactions of the characters. Using qualitative methods with content analysis, data were obtained from in-depth observations of several key scenes and supported by literature on Marxism, social criticism, and digital culture. The results show that humor in Mutant works through three main layers: (1) class representation, (2) critique of conformity culture, and (3) commodification of identity. Thus, this study confirms that Mutant functions not only as entertainment, but also as a medium of social criticism that reveals the mechanisms of domination and resistance in contemporary society. These findings contribute to the expansion of the study of literary sociology in the context of digital culture and open up new reading spaces for humor as a means of social reflection.